PENGARUH NOVEL DILAN TERHADAP KARAKTER SISWA DILIHAT DARI TOKOH DILAN - Usman Rasyidin; Fahmi Saeful Aziz; Dida Firmansyah (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
This novels research Dilan aims to describe the character of students of to Novel Dilan seen from Dilan figure and how far the author's involvement in Novel Dilan. This research is the influence of Dilan novel that is a Qualitative method. Research Techniques include data collection phase, data analysis, data presentation and conclusion drawing. Sources of data from primary data (Novel Dilan) and secondary form of literature and other sources. Psycholinguistic research has an important role in providing feedback on the character developed in analyzing a strong literary work with psychological problems. The results showed psycholinguistic aspects are imitations of children today, where many children enter motorcycle gangs, neglected lessons and much more courtship school. The results of the questionnaire there are 3 aspects of the first aspect entitled Aspects of Character Novel Dilan 54.6%, this indicates that the reader aspects of novel characters Dilan the story is very reasonable. The second aspect of Dilan figure with the result is 54% indicating that respondents really like against the figure of Dilan, while the third aspect entitled Event Aspects that occur with the result is 40.66%.From 3 Aspects concluded that the novel Dilan affected for the student.